Balancing Short-Term and Long-Term Strategies in Collaboration - Rydén, Malin; Karlsson, Ella (My University, 2022)
For a B2B startup, its collaborations and how these are managed is what affects the current and future possibilities. Established corporations and startups have shown to be co-dependent on each other in order to develop innovative products in various industries. The food industry can be seen as one of the oldest in the world and because of climate change and a growing population, the industry faces new challenges to meet the future demands. There is a shift towards a more open innovation mindset, where new companies are entering the industry. When an innovative B2B startup enters, they must adapt to working with established actors. As startups and established firms portray different organisational structures, collaborations entail several challenges, especially when they are impacted by traditional market structures. In addition, a startup’s limited resources implies that great consideration must be made into what collaborative actions are made and how they are prioritised. From this context, this thesis was aimed at understanding how B2B startups in the food industry manage the balance of several collaborations and to simultaneously examine how this affects the consideration between short term and long-term strategies. An abductive approach with a single-case design was used as the method for this qualitative thesis. Interviews and observations were made at a case company and the collected data was later analysed and interpreted within a theoretical framework. The findings indicate that a B2B startup separates collaborations depending on if they fulfil a short- or long-term purpose. To find a balance between these can be crucial for companies’ survival, but hard to achieve when resources are limited. Managing collaborations have been seen to be greatly affected by how expectations are set and not aligning these between actors can be devastating for the outcome of a potential collaboration. The setting of the Swedish food industry also entails a B2B startup to tackle a power imbalance between an established firm’s resources and a startup’s innovativeness. This ability to innovate can also be hindered by the regulations of the industry, together with incumbents’ lacking knowledge of new technologies and following precautions to secure intellectual property. It is concluded that the characteristics of the food industry impedes innovative collaborations between diverse actors. However, ecosystem innovation is argued to be a possible tool to support the advancement of collaborative and open innovation.
Keywords: start-up; collaboration; foodtech; food industry; long-term; short-term; business to business (B2B); business strategy; innovation